Síntese e caracterização de revestimentos híbridos em aço A36 para aplicações anticorrosivas - Clemente, Guilherme Augusto Bertelli Fernandes (2021)
In the constant search for uniform materials capable of coating metal surfaces and protecting them from the attack of corrosion, industrial painting techniques stand out for their versatility, ease of application and maintenance, and low cost. Steel is a metallic material widely used by industry in different types of segments, and corrosion is a pathology responsible for its functional loss. In this context, hydrophobic materials can help considerably since they have as a functional characteristic, resistance to moisture, thus reducing corrosion. This work aimed to prepare coatings using the solgel process, as a possible alternative for anti-corrosive coatings on metal surfaces. For this, precursor solutions containing different concentrations of water, ethanol, tetraethylorthosilicate, to form silica, cetitrimethyl ammonium bromide, as a pore director, and polyetheramine, to increase hydrophobicity, were prepared and then the coatings were deposited in different speeds by the dip-coating technique on borosilicate and A36 steel substrates. The coatings were characterized by X-ray diffraction and scanning electron microscopy. In the coatings deposited on the borosilicate substrate, it was possible to notice the formation of a more ordered network of pores with a cubic arrangement for a speed of 300 mm/min and that the addition of polyetheramine in the amounts of 0.001 and 0.005 mol led to the obtainment of more films. homogeneous. For the coatings deposited on the A36 steel substrate, the parameters previously optimized were used and the influence of the cleaning process and the addition of cetyltrimethyl ammonium bromide on the structural and macroscopic properties of the coatings were evaluated. From the results it can be observed that the presence of nitric acid in the cleaning process and the presence of cetyltrimethyl ammonium bromide in the precursor solution caused the appearance of signs of corrosion on the substrate. In addition, after corrosion tests both with marine water and with exposure to weathering, signs of corrosion were not observed in the substrates that contained the coatings deposited from immersion in the precursor solution for 24 hours. Only the coatings deposited at a speed of 300 mm/min showed signs of corrosion. This fact could be attributed to the difference in the thickness of the coverings. Finally, tests to evaluate the hydrophobicity of the coatings showed that samples with a higher amount of PPO400 and shorter coating deposition time are less hydrophilic. Keywords: sol-gel, hydrophobic films, mesoporous silica, dip-coating, PPO400.